Balloon-Guide Catheters Are Needed for Effective Flow Reversal during Mechanical Thrombectomy - Nikoubashman, O.; Wischer, D.; Hennemann, H.M.; Sandmann, J.; Sichtermann, T.; Müschenich, F.S.; Reich, A.; Wiesmann, M. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Blood flow management in the carotid artery during mechanical thrombectomy is crucial for safety and effectiveness. There is an ongoing discussion about whether balloon-guide catheters or large-bore sheaths are needed for effective flow management. We compared general flow characteristics of proximal aspiration through a large-bore sheath and a balloon-guide catheter in a porcine in vivo model.MATERIALS AND METHODS: We investigated blood flow in a porcine common carotid artery with and without aspiration (VacLok syringe and Penumbra pump, Pump MAX) through an 8F-long sheath and an 8F balloon-guide catheter. Blood hemodynamics were assessed via continuous duplex sonography.RESULTS: Average vessel diameter and baseline blood flow were 4.4 ± 0.2 mm and 244 ± 20 mL/min, respectively. For the 8F sheath, pump aspiration resulted in a significant flow reduction (225 ± 25 mL/min, P < .001), but with a persisting antegrade stream. Manual aspiration resulted in collapse of the vessel in 2 of 7 measurements and oscillatory flow with antegrade systolic and retrograde diastolic components in the remaining 5 measurements. Net flow was antegrade (52 ± 44 mL/min) in 3 and retrograde (−95 ± 52 mL/min) in the remaining 2 measurements. For balloon-guide catheters, balloon inflation always resulted in flow arrest. Additional pump or manual aspiration resulted in significant flow reversal of −1100 ± 230 and −468 ± 46 mL/min, respectively (both, P < .001).CONCLUSIONS: Only balloon-guide catheters allow reliable blood flow arrest and flow reversal in combination with aspiration via syringes or high-flow pump systems. Aspiration through an 8F sheath results in either collapse of the vessel or oscillatory flow, which can result in a net antegrade or retrograde stream.BGCballoon-guide catheterCCAcommon carotid artery